Development of a “green” economy: World experience - Rakhmanbaeva Roza; Yekimov Sergey; Šálková Daniela (E3S Web of Conferences, 2023)
This scientific article examines the world experience in the development of a "green" economy. The transition to a “green” economy in the world community is demand of the time and real reality. Among the main factors determining the extent to which states are involved in this process are the scarcity of resources and the level of their pollution, the presence of political will at the highest level and public support for government initiatives. Keywords: green economy, natural resources, air pollution, environment, pollution index, agricultural land, water resources, energy.